2012
DOI: 10.2500/ajra.2012.26.3711
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Complications of Endoscopic Sinus Surgery for Chronic Rhinosinusitis

Abstract: The risk factors for perioperative complications were asthma and the polyp score. We conclude that the surgeon should confirm whether the patient has lower airway disease, especially asthma, before operating. The surgeon should also determine the grade of nasal polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 22 publications
(23 reference statements)
8
54
1
3
Order By: Relevance
“…The prospective study conducted by Hopkins et al 5 in 2006 reported their overall, major, and minor complication rates of 7.0%, 0.4%, and 6.6%, respectively. Asaka et al 12 total complication rates ranging from 0.3% to 22.4%, major complication rates ranging from 0% to 1.5%, and minor complication rates ranging from 1.1% to 20.8%. Conclusively, the rate of major complications of ESS has generally been low, and our result was consistent with this broader finding.…”
Section: Discussionmentioning
confidence: 97%
“…The prospective study conducted by Hopkins et al 5 in 2006 reported their overall, major, and minor complication rates of 7.0%, 0.4%, and 6.6%, respectively. Asaka et al 12 total complication rates ranging from 0.3% to 22.4%, major complication rates ranging from 0% to 1.5%, and minor complication rates ranging from 1.1% to 20.8%. Conclusively, the rate of major complications of ESS has generally been low, and our result was consistent with this broader finding.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies found that nasal polyposis is a risk factor for surgical complications. [12][13][14] Due to the limitations of the data set, we were only able to analyze major complications with specific diagnosis codes that occurred at the time of surgery and were not able to analyze minor complications such as epistaxis or longer-term complications such as readmission, synechiae formation, and stenosis.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10][11] Patients with CRSwNP may also have a higher risk of complications during surgery due to increased bleeding, decreased visualization, and altered anatomy. [12][13][14] The objectives of this study were to (1) determine the percentage of surgeries performed for CRSwNP compared with CRSsNP in an administrative data base that records all ambulatory surgeries, (2) compare the demographic information of patients who underwent procedures performed for CRSwNP compared with CRSsNP, (3) determine the extent of surgical interventions commonly performed for the diagnosis of CRSwNP compared with CRSsNP, and (4) calculate the rate of complications and the mean charges and operating room (OR) times for procedures for patients with CRSwNP compared with those with CRSsNP.…”
Section: Hronic Rhinosinusitis (Crs) Is Characterized By Mucosal Inmentioning
confidence: 99%
“…Asaka et al 1360 performed a prospective study on 706 patients undergoing ESS for CRS. The overall complication rate in this group of patients was 5.8% (41/706).…”
Section: S169mentioning
confidence: 99%